Automated design of structures and compliant mechanisms by topological optimization - Chee, Tat Hon. (2008)
Compliant mechanisms are a class of mechanisms that achieve desired force and motion transmission by undergoing elastic deformations, in contrast to rigid-body displacements in the conventional rigid-link mechanisms. Most of the previously reported design synthesis studies in distributed fully-compliant mechanisms involve structural topology optimization using homogenization and mathematical programming, creating designs with ill connected elements and intermediate densities that raise ambiguity in determining the final contour of the structure. This research attempts to present a new synthesis procedure for structural topology optimization using genetic algorithm-based search technique and Bezier curve representation of the physical structure that draws analogy from skeleton and flesh arrangement of many organisms.